Variation in faecal testosterone levels in male gray whales on a foraging ground relative to maturity and timing - Fernandez Ajó, Alejandro; Buck, C Loren; Hunt, Kathleen; Pirotta, Enrico; New, Leslie; Dillon, Danielle; Bierlich, KC; Hildebrand, Lisa; Bird, Clara; Torres, Leigh (Conservation Physiology, 2025)
Funding: This project was supported by the NOAA National Marine Fisheries Service Office of Science and Technology, the Office of Naval Research Marine Mammals and Biology program [grant number: N00014-20-1-2760], and the Oregon State University Marine Mammal Institute, and Oregon Sea Grant [grant number: RECO-40-PD]. Understanding wildlife reproductive seasonality is crucial for effective management and long-term monitoring of species. This study investigates the seasonal variability of testosterone in male Pacific Coast Feeding Group (PCFG) gray whales, using an eight-year dataset (2016–2023) of individual sightings, drone-based photogrammetry and endocrine analysis of faecal samples. We analyzed the relationship between faecal testosterone levels and total body length (TL), body condition (body area index, BAI), sexual maturity and day of the year using generalized additive mixed models. Our findings reveal a significant increase in faecal testosterone levels in mature males (MM) towards the end of the foraging season. This increase was not observed in JM, highlighting age-dependent development of sexual characteristics. No significant relationship was found between testosterone levels and TL. Additionally, BAI was not significantly associated with testosterone levels. Our results suggest that the increasing testosterone levels in MM gray whales may indicate preparation for mating before the southbound migration. These findings provide valuable insights into the reproductive biology of PCFG gray whales and underscore the importance of non-invasive faecal sampling for studying reproductive seasonality in large whales. Our approach not only provides further insights into the seasonality of male reproduction for the PCFG gray whales but also offers tools to enhance the understanding of male reproduction in baleen whales broadly with non-invasive approaches. Peer reviewed